Uwagi na temat sejmików szlachty sieradzkiej w Szadku na początku XVIII w. - na marginesie laudum z 8 czerwca 1716 r. - Florczak, Ilona (Biuletyn Szadkowski, 2013)
From the 14th to the end of the 18th century, Szadek was the place where political sejmiks of the Sieradz Voivodeship were held (exeptions were the election sejmiks, which took place in Sieradz). This article foccuses on the reasons why Szadek was chosen as a place of Sieradz Voivodeship sejmiks. It also discusses the role which sejmiks played in local life and shows the political and economic situation of this land at the beginning of the 18th century, connected with economic crisis, epidemics, political chaos and the Northem War. These were the reasons why Sieradz Voivodeship nobility joined the Confederetion in Targowica in 1716. The article also presents the resolution of the confederate sejmik of Sieradz Voivodeship Nobility, adopted in Szadek on 8th June 1716. This source document, being part of the collection of the Bartoszewicz family, is kept in the State Archive in Łódź.